ISOLASI DARI 8-HIDROKSI-6,7-DIMETHOKSI KUMARIN DAN TOKSISITAS BATANG JARAK TINTIR (Jatropha multifida L.) MENGGUNAKAN BRINE SHRIMP LETHALITY TEST (BSLT) - Akhirul Kahfi Syam; Muhamad Insanu; Komar Ruslan Wirasutisna (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Jatropha multifida L. (jarak tintir) was a shrub, annual, and had ± 2 m high. Empirically jarak tintir sap was used as traditional medicine by Indonesian people for a long time. Only limited studies were conducted regarding its chemical compound. It was reported that multifidone (diterpenoid compound from the stem) had an activity against cancer cells in vitro. This study aimed to test the toxicity of various extracts (n-hexane, ethyl acetate, and methanol) with Brine Shrimp Lethality Test (BSLT) of Jatropha multifida L. stem. A Fraxidin (8-hidroxy-6,7-dimethoxy coumarin) has been isolated from ethyl acetate fraction based on highest cytotoxic with LC50 value 3.69 µg/mL. The isolated compound was elucidated to gain chemical structure base on spectroscopic data (UV-Vis Spectrofotometric, IR Spectrofotometric, and NMR). Toxicity of fraxidin was tested on BSLT and showed no potential activity with LC50 value > 500 μg/mL.